The Demise of the Copyright Act in the Digital Realm: Re-Engineering Digital Delivery Models to Circumvent Copyright Liability After Aereo - Larkin, Megan (The Columbia Journal of Law & the Arts, 2014)
This Note argues that the Second Circuit’s interpretation of the Transmit Clause eviscerates the meaning of “public” within the digital realm and has created a blueprint for business models to completely circumvent copyright liability. Part I provides the background of the public performance right, focusing on the role that technology has played in the addition of the Transmit Clause and on relevant judicial interpretation. Part II argues that the Second Circuit’s interpretation of the Transmit Clause was improper; it tests the court’s blueprint by re-engineering past business models to show how they could have evaded liability. Part III proposes that, in order to prevent the breakdown of traditional copyright protection in the digital realm, courts should prioritize function over form and adopt a delivery-agnostic approach to evaluating copyright infringement.